Semiotic Networks of Pan-Asian Cultural Communication: Rabindranath Tagore, Javanese Batik, and the 1927–2027 Inter-Asian Encounter - Komarudin Kudiya; Saftiyaningsih Ken Atik (Mediator: Jurnal Komunikasi, 2026)
This study examines how Javanese batik operates as a visual semiotic medium within Pan-Asian cultural communication by revisiting Rabindranath Tagore’s 1927 encounter with Java and its centenary relevance in 2027. Existing studies of Pan-Asian encounters often privilege textual, literary, and historical narratives, while the communicative role of visual and material culture remains less fully theorized. Using an interpretative qualitative approach, this study analyzes selected Javanese batik artifacts, Tagore’s travel writings, and historical accounts through semiotic and iconological readings, supported by comparative interpretation and source triangulation. The findings identify three interconnected dimensions of semiotic networks: the circulation of cosmological symbols, the articulation of spiritual-aesthetic values, and the negotiation of philosophical meanings across cultural boundaries. Rather than treating Tagore’s encounter with batik as a one-directional transmission of influence, the study conceptualizes it as a dialogical process in which visual symbols, material practices, and cultural memory interact. The article contributes to cultural communication studies by proposing semiotic networks as a framework for analyzing non-verbal and relational communication in Asian contexts. It also highlights practical implications for cultural diplomacy, heritage communication, and tradition-based design innovation by positioning batik as an active medium of intercultural dialogue.